Assessment of enamel demineralization, shear bond strength, and failure mode following the use of orthodontic adhesive containing silver nanoparticles: an in-vitro study - Almosa, Naif; Alsaleh, Ahmed; Alnowaiser, Alhanouf; Alhogail, Nada; Alsuliman, Abdalaziz; Alswailem, Latifa; Zawawi, Rahaf; Habib, Syed Rashid (Frontiers in Materials, 2025)
ObjectiveThis study evaluated enamel demineralization, shear bond strength, and failure modes associated with orthodontic adhesives containing silver nanoparticles (AgNPs).MethodsForty-eight extracted human premolar teeth were selected and evenly divided into two groups based on the intended assessments, with 28 specimens in each group: Part I focused on enamel demineralization depth, and Part II addressed shear bond strength and failure modes. Specimens were prepared, mounted, and bonded using two adhesive systems: Group A used a conventional adhesive system without AgNPs, while Group B employed a conventional adhesive system mixed with AgNPs. In Part I, specimens underwent artificial demineralization at pH 4.5°C and 37°C for 7 days, followed by buccolingual sectioning. The depth of demineralization was measured using a scanning electron microscope and analyzed with ImageJ software. In Part II, shear bond strength was assessed using a universal testing machine, followed by failure mode evaluation using a stereomicroscope.ResultsResults showed that Group A exhibited a significantly greater demineralization depth compared to Group B (p = 0.000). However, no significant difference was observed between overall location levels (p = 0.093). Additionally, Group B demonstrated significantly higher shear bond strength (p = 0.000) and a more uniform distribution of failure modes compared to Group A.ConclusionsThese findings suggest that incorporating silver nanoparticles into orthodontic adhesives reduces demineralization depth and enhances shear bond strength compared to conventional adhesive systems. In contrast, conventional adhesives were associated with a higher incidence of adhesive mode failure.